Metode Istinbat Nahdlatul Ulama: Kajian Tentang Bahtsul Masail - Luthfi Hadi Aminuddin (Justicia Islamica, 2005)
This study aims to examine the legal istinbat method used in the Bahtsul Masail Nahdlatul Ulama (NU) forum. Bahtsul Masail is a legal decision-making mechanism unique to NU, which refers to turats (classical) books and considers the social context. This study uses a qualitative method with a descriptive-analytical approach, based on a study of literature and an analysis of official NU documents related to Bahtsul Masail. The results show that the istinbat method in NU is not only based on classical fiqh texts but also considers the maqashid of sharia and the needs of the ummah. This approach allows for flexibility in responding to contemporary issues without leaving the established corridors of Islamic scholarship. Thus, Bahtsul Masail becomes an important instrument in maintaining the relevance of Islamic law to ever-evolving social dynamics.